Supply Chains in Network Economy - Fiala, Petr (Communications - Scientific Letters of the University of Zilina, 2003)
A supply chain can be shown as a set of units interconnected by material, financial, information and decision flows from initial suppliers to ultimate customers. Supply chain management is more and more affected by network business environment and by information and communication technologies. The paper analyzes a combination of non-cooperative and cooperative decision making of supply chains in network economy.
Keywords: supply chain; network economy; e-commerce; non-cooperative and cooperative decision-making